2016
DOI: 10.1161/jaha.116.003725
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Dabigatran, Rivaroxaban, and Apixaban Versus Warfarin in Nonvalvular Atrial Fibrillation

Abstract: BackgroundThe introduction of non–vitamin K antagonist oral anticoagulants has been a major advance for stroke prevention in atrial fibrillation; however, outcomes achieved in clinical trials may not translate to routine practice. We aimed to evaluate the effectiveness and safety of dabigatran, rivaroxaban, and apixaban by comparing each agent with warfarin.Methods and ResultsUsing a large US insurance database, we identified privately insured and Medicare Advantage patients with nonvalvular atrial fibrillatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
284
3
18

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(336 citation statements)
references
References 74 publications
(149 reference statements)
31
284
3
18
Order By: Relevance
“…However, the risk of death or all major bleeding was significantly higher for warfarin and rivaroxaban versus apixaban and dabigatran 22. Yao et al23 evaluated the efficacy and safety of 3 NOACs by comparing each agent with warfarin using a large US insurance database. Their results indicated that apixaban had lower risks of both stroke and major bleeding and dabigatran had a similar risk of stroke but a lower risk of major bleeding, while rivaroxaban had similar risks of both stroke and major bleeding compared with warfarin 23.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the risk of death or all major bleeding was significantly higher for warfarin and rivaroxaban versus apixaban and dabigatran 22. Yao et al23 evaluated the efficacy and safety of 3 NOACs by comparing each agent with warfarin using a large US insurance database. Their results indicated that apixaban had lower risks of both stroke and major bleeding and dabigatran had a similar risk of stroke but a lower risk of major bleeding, while rivaroxaban had similar risks of both stroke and major bleeding compared with warfarin 23.…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al23 evaluated the efficacy and safety of 3 NOACs by comparing each agent with warfarin using a large US insurance database. Their results indicated that apixaban had lower risks of both stroke and major bleeding and dabigatran had a similar risk of stroke but a lower risk of major bleeding, while rivaroxaban had similar risks of both stroke and major bleeding compared with warfarin 23. Graham et al24 conducted a retrospective new‐user cohort study with enrollment of 118 891 patients with NVAF using the US Medicare system 24.…”
Section: Discussionmentioning
confidence: 99%
“…As a whole, these studies confirm that in older patients DOACs are at least as effective as VKAs in preventing ischemic stroke and thromboembolism, and are associated with a consistent reduction in the risk of intracranial bleeding. However, safety data on major extracranial bleedings appear to be highly heterogeneous between different DOACs in these studies, with current evidence suggesting an apparent better safety profile for AP and low dose DA [95][96][97][98][99].…”
Section: Evidence From Real-world Studiesmentioning
confidence: 94%
“…El momento de reintroducir la anticoagulación no está bien definido; en algunos estudios se propone reintroducir cuando haya estabilidad hemodinámica 18 y en otros a partir del cuarto día tras el diagnóstico 19 . Hay que resaltar que el 57% de nuestros pacientes en tratamiento con acenocumarol presentaban INR en rango supraterapéutico, por lo que se debe insistir en la recomendación de controlar de forma estrecha las dosis de acenocumarol para evitar complicaciones hemorrágicas y, en pacientes con INR lábil o elevado riesgo de sangrado, plantear otras alternativas terapéuticas como los anticoagulantes de acción directa 12,[20][21][22][23][24][25][26] . La insuficiencia renal es un factor de riesgo de complicaciones hemorrágicas en pacientes anticoagulados y recientemente se ha señalado como el segundo factor de riesgo de HEMR después de la anticoagulación al estar presente en el 58% de los casos en una serie de 115 pacientes 3 .…”
Section: Discussionunclassified